Metodika kontrolya spetsial'noi vynoslivosti v tsiklicheskikh vidakh sporta s uchyetom moshchnosti i yemkosti energeticheskikh mekhanizmov - Sanosyan, Kh. A.; Kochikyan, A. A.; Arakelyan, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
Training under modern social cnditions demands for new methods of training control. One ressource is the training control by analysis of energetic mechanisms.